Luxury fashion marketing and branding : a strategic approach - Dallabona, Alice (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Luxury Fashion Marketing and Branding offers a comprehensive analysis of the key theories and concepts needed to understand the promotion of luxury fashion products. It covers subjects including luxury fashion retailing, digital marketing and communication, data analytics, emerging technologies, consumer behaviour and PR. The textbook also offers a focused discussion of the challenges faced by luxury fashion brands to meet growing customer demand for ethical and sustainable practice, including concerns related to diversity, inclusivity, and cultural sensitivity. This textbook is grounded in business practices, featuring real-world examples and international case studies from both established and modern brands. Chapter objectives and summaries aid comprehension, whilst end-of-chapter questions and activities enable further research and discussion. Luxury Fashion Marketing and Branding is ideal for advanced undergraduate and postgraduate students of fashion marketing and communications, luxury fashion business and luxury brand management. Its applied approach will also make it suitable for those studying for an Executive MBA in Fashion and Luxury Management. Online resources include an instructor's manual, lecture slides and a test bank"--
Keywords: Fashion merchandising; Branding (Marketing); BUSINESS & ECONOMICS / Industries / Textile Industry; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing